Para além dos muros do processo seletivo: análise das propostas de produção de textos nos vestibulares de universidades públicas paulistas - De Lazzari, Fabiana Parra (2017)
The purpose of this study is to profile the proposals of text production from the Brazilian vestibulares (university entrance exams) that are considerably pursued/competitive, in order to provide teachers the conditions for a more complete pedagogical orientation regarding the productions of texts to be performed by candidates in these vestibulares. It is also the objective of this study to investigate whether these identity characteristics are consistent with the context of the candidates in each one of the vestibulares here studied and to assess if such identity characteristics allow a comprehensive and complete evaluation of the candidates. The corpus of the present study includes the vestibulares between the years of 2012 and 2015 for admissions into the Universidade de São Paulo (prepared by the Fundação Universitária para o Vestibular), the Universidade Estadual Paulista Júlio de Mesquita Filho (prepared by the Fundação para o Vestibular da Unesp), and the Universidade Estadual de Campinas (prepared by the Comissão Permanente para os Vestibulares). The method for our analyses is based on the triad Descriptions-Comparisons-Weighting. The reference for the analyses is Textual Linguistics. We also make use of theoretical contributions from studies of Rhetoric and New Rhetoric